ShenLian Extract Enhances TGF-β Functions in the Macrophage-SMC Unit and Stabilizes Atherosclerotic Plaques - Liu, Li; Li, Qi; Yin, Jie; Zhao, Zheng; Sun, Lidong; Ran, Qingsen; Du, Xinke; Wang, Yajie; Li, Yujie; Yang, Qing; Chen, Ying; Weng, Xiaogang; et al. (Frontiers in Pharmacology, 2021)
Background/Aim: Macrophage polarization and phenotypic switching of smooth muscle cells (SMCs) are multi-faceted events dominating atherosclerosis (AS) progression. TGF-β was proved to been one of the bridge on the crosstalk between macrophage and SMC. ShenLian (SL) was extracted from a potent anti-atherosclerotic formula. However, its exact mechanism rebalancing inflammatory microenvironment of AS remain largely unknown. Within the entirety of macrophage and SMC, this study investigated the pharmacological effects of SL on stabilizing atherosclerotic plaques. Methods: The main components of SL were examined by high performance liquid chromatography. Co-culture and conditioned medium models of macrophage/SMC interactions were designed to identify the relationship between macrophage polarization and switching of SMC phenotypes. Flow cytometry, immunofluorescent staining, RT-PCR, western blotting, and ELISA were used to determine the expression of molecules relating to AS progression. An atherosclerosis animal model, established by placing a perivascular collar on the right common carotid artery in ApoE-/- mice, was used to investigate whether TGF-β is the key molecular mediator of SL in crosstalk between macrophage and SMC. Plaque size was defined by nuclear magnetic resonance imaging. Key markers related to phenotypic transformation of macrophage and SMC were determined by immunohistochemical staining. Results: Results revealed that, accompanied by rebalanced M2 macrophage polarization, SL supported SMC phenotypic transformation and functionally reconstruct the ECM of plaques specifically in macrophage-SMC co-cultural model. Molecularly, such activity of SL closely related to the activation of STAT3/SOCS3 pathway. Furthermore, in co-culture system, up-regulation of α-SMA induced by SL could neutralized by 1D11, a TGF-β neutralizing antibody, indicating that SL mediated Macrophage-SMC communication by enhancing TGF-β. In the AS model constructed by ApoE-/- mice, effects of SL on phenotypic transformation of macrophage and SMC has been well verified. Specific blocking of TGF-β largely attenuated the aforementioned effects of SL. Conclusion: Our findings highlighted that TGF-β might be the responsive factor of SL within macrophage and SMC communication. This study revealed that crosstalk between macrophage and SMC forms a holistic entirety promoting atherosclerotic plaque stability.